Epidemiology of sudden unexpected natural medicolegal deaths in Jammu region of union territory of Jammu and Kashmir - Sandhya Arora,; Maini, Vinka; Deepa Hans, (Asian Journal of Medical Sciences, 2022)
Background: Medicolegal autopsies are conducted in cases of sudden and unexpected deaths primarily to establish the cause of death in cases where such deaths have occurred in apparently healthy individuals under suspicious circumstances. Aims and Objectives: The current study was done to analyze autopsies of individuals dying of sudden death. Materials and Methods: A retrospective, case record study on cases of natural deaths brought for medicolegal autopsies to the mortuary was studied. The findings were statistically analyzed using descriptive statistics to find out the mean, percentage, and frequencies. Results: In the present study, a total of 70 sudden unexpected natural medicolegal deaths were studied. Male (92.86%) was more than females (7.14%) and male: female ratio was 13:1. The most common age group was 51–60 years (40%) followed by 41–50 years (35.71%). System-wise cardiovascular system involvement was most common (54.29%), followed by respiratory system (14.29%), central nervous system (10%), gastrointestinal tract (8.57%), genitourinary system (2.86%), septicemia (2.86%), and miscellaneous (7.14%) were noted. Coronary artery disease (51.43%) was most common disease noted, followed by tuberculosis (10%), intraventricular hemorrhage (10%), cirrhosis (7.14%), pneumonia/bronchiolitis (4.29%), cardiomyopathy (2.86%), septicemia (2.86%), ruptured ectopic pregnancy (1.43%), and chronic pyelonephritis (1.43%) were noted as cause of death. Conclusion: Cardiovascular disease accounts for the maximum number of sudden deaths, in which coronary artery disease is the main cause of sudden deaths.